Echinacea purpurea and Onopordum acanthium Combined Extracts Cause Immunomodulatory Effects in Lipopolysaccharide-Challenged Rats - Maria Vlasheva; Mariana Katsarova; Ilin Kandilarov; Hristina Zlatanova-Tenisheva; Petya Gardjeva; Petko Denev; Nora Sadakova; Viktor Filipov; Ilia Kostadinov; Stela Dimitrova (Plants)
Echinacea purpurea and Onopordum acanthium, which belong to the Asteraceae family, are widely used plants in traditional medicine. Their antioxidant, anti-inflammatory, antiviral, antibacterial, and antitumor effects are well known. However, there are no data on the effects of their combination. The aim of the present study was to combine E. purpurea with O. acanthium to study the in vivo immunomodulatory effect of two combinations and to compare it with that of single plants. Their total polyphenolic and flavonoid content and the amounts of individual compounds characteristic of both species were determined. The influence of the obtained extracts on the serum concentrations of cytokines IFN-γ, TNF-α, and IL-10 in experimental animals with lipopolysaccharide-induced systemic inflammatory response was investigated. This research found that a combination of E. purpurea/O. acanthium in the ratio 1:1 reduced the proinflammatory cytokines TNF-α (244.82 pg/mL) and IFN-γ (1327.92 pg/mL) compared to the LPS-control, respectively, (574.17 pg/mL) and (3354.00 pg/mL), and the combination E. purpurea/O. acanthium in the ratio of 3:1 significantly increased the levels of the anti-inflammatory cytokine IL-10 (1313.95 pg/mL) compared to the LPS-control (760.09 pg/mL). In conclusion, our results could be a basis for future biomedical research on creating phytopreparations with an immunomodulatory effect.